2020
DOI: 10.3390/inventions5020018
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Simulations for Floating Darrieus-Type Wind Turbines with Three-Stage Rotors

Abstract: Growing energy demand is causing a significant decrease in the world’s hydrocarbon stock in addition to the pollution of our ecosystem. Based on this observation, the search for alternative sorts of energy to fossil fuels is being increasingly explored and exploited. Wind energy is experiencing a very important development, and it offers a very profitable opportunity for exploitation since the wind is always available and inexhaustible. Several technical solutions exist to exploit wind energy, such as floating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Darrieus turbine in this study uses the NACA 0030, with variations in the pitch angle as shown in Figure 1, wherein each test of the pitch angle remains the same throughout the turbine rotation. This Darrieus turbine blade was chosen because it has the best performance based on its shape with no basin to increase the thrust [27]. Besides, based on Subramanian et al [28], who examined the Darrieus turbine using CFD simulations, obtained that the best value of Cp and TSR was NACA 0030.…”
Section: Methods Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Darrieus turbine in this study uses the NACA 0030, with variations in the pitch angle as shown in Figure 1, wherein each test of the pitch angle remains the same throughout the turbine rotation. This Darrieus turbine blade was chosen because it has the best performance based on its shape with no basin to increase the thrust [27]. Besides, based on Subramanian et al [28], who examined the Darrieus turbine using CFD simulations, obtained that the best value of Cp and TSR was NACA 0030.…”
Section: Methods Materialsmentioning
confidence: 99%
“…The ratio between the mechanical power of the rotor and the mechanical power of the wind passing through the rotor, described as follows (27,35):…”
Section: Equation Designmentioning
confidence: 99%
See 3 more Smart Citations